(untitled) (The Review of Diabetic Studies, 2023)
Islet autoimmunity in type 1 diabetes results in the loss of the pancreatic β-cells. The consequences of insulin deficiency in the portal vein for liver fat are poorly understood. Under normal conditions, the portal vein provides 75% of the liver blood supply. Recent studies suggest that non-alcoholic fatty liver disease (NAFLD) may be more common in type 1 diabetes than previously thought, and may serve as an independent risk marker for some chronic diabetic complications. The pathogenesis of NAFLD remains obscure, but it has been hypothesized that hepatic fat accumulation in type 1 diabetes may be due to lipoprotein abnormalities, hyperglycemia-induced activation of the transcription factors carbohydrate response element-binding protein (ChREBP) and sterol regulatory element-binding protein 1c (SREBP-1c), upregulation of glucose transporter 2 (GLUT2) with subsequent intrahepatic fat synthesis, or a combination of these mechanisms. Novel approaches to non-invasive determinations of liver fat may clarify the consequences for liver metabolism when the pancreas has ceased producing insulin. This article aims to review the factors potentially contributing to hepatic steatosis in type 1 diabetes, and to assess the feasibility of using liver fat as a prognostic and/or diagnostic marker for the disease. It provides a background and a case for possible future studies in the field.